Essays on China's outward foreign direct investment: 1991-2009 - Wang, Pan (2012)
China’s outward foreign direct investment (OFDI) grew from a very limited scale prior to the 1990s to reach an annual average growth rate of 67% between 1991 and 2009, placing China as the largest FDI source country among the developing countries, and the fifth largest FDI source country in the world in 2009. China’s experience is particularly interesting because it serves to help us further understand OFDI in general and the emergence of investments from the developing countries in particular. This thesis aims to answer a series of unexplored questions about China’s OFDI, including its underlying motivations and locational determinants, the dynamic adjustment of China’s OFDI and its relationship with China’s inward foreign direct investment (IFDI), as well as the displacement effect of China’s OFDI on the OECD’s OFDI in the host countries.